Overcoming Shellfish Allergy: How Far Have We Come? - Wai, Christine Y.Y.; Leung, Nicki Y.H.; Chu, Ka Hou; Leung, Patrick S.C.; Leung, Agnes S.Y.; Wong, Gary W.K.; Leung, Ting Fan (International journal of molecular sciences, 2020)
Shellfish allergy caused by undesirable immunological responses upon ingestion of crustaceans and mollusks is a common cause of food allergy, especially in the Asia-Pacific region. While the prevalence of shellfish allergy is increasing, the mainstay of clinical diagnosis for these patients includes extract-based skin prick test and specific IgE measurement while clinical management consists of food avoidance and as-needed use of adrenaline autoinjector should they develop severe allergic reactions. Such a standard of care is unsatisfactory to both patients and healthcare practitioners. There is a pressing need to introduce more specific diagnostic methods, as well as effective and safe therapies for patients with shellfish allergy. Knowledge gained on the identifications and defining the immuno-molecular features of different shellfish allergens over the past two decades have gradually translated into the design of new diagnostic and treatment options for shellfish allergy. In this review, we will discuss the epidemiology, the molecular identification of shellfish allergens, recent progress in various diagnostic methods, as well as current development in immunotherapeutic approaches including the use of unmodified allergens, hypoallergens, immunoregulatory peptides and DNA vaccines for the prevention and treatment of shellfish allergy. The prospect of a “cure “for shellfish allergy is within reach.